2005
DOI: 10.3758/bf03193533
|View full text |Cite
|
Sign up to set email alerts
|

Location negative priming in identity discrimination relies on location repetition

Abstract: Negative priming manifests when a previously ignored stimulus becomes a target. The contingency of identity negative priming on repeated stimuli has been demonstrated, implying a crucial role for distractor competition. In this study, a naming task was used to examine whether location negative priming also relies on the repetition of locations. In Experiment 1, location negative priming was observed only when a small set of repeated locations was used. Positive priming was found instead when a large set of non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…According to the activation model of Malley and Strayer (1995); see also Strayer and Grison (1999), when a stimulus is repeatedly used in an experiment, it should have higher activation and competes with target processing to a greater extent than a nonrepeated stimulus does. As a result, the negative priming eVect is easier to be observed with repeated rather than nonrepeated stimuli (Chao & Yeh, 2005;Kramer & Strayer, 2001;Malley & Strayer, 1995;Strayer & Grions, 1999). Therefore, it should be more diYcult to select a target when its distractor was a well practiced, highly familiar stimulus.…”
Section: Methodsmentioning
confidence: 92%
“…According to the activation model of Malley and Strayer (1995); see also Strayer and Grison (1999), when a stimulus is repeatedly used in an experiment, it should have higher activation and competes with target processing to a greater extent than a nonrepeated stimulus does. As a result, the negative priming eVect is easier to be observed with repeated rather than nonrepeated stimuli (Chao & Yeh, 2005;Kramer & Strayer, 2001;Malley & Strayer, 1995;Strayer & Grions, 1999). Therefore, it should be more diYcult to select a target when its distractor was a well practiced, highly familiar stimulus.…”
Section: Methodsmentioning
confidence: 92%
“…However, in negative priming, the inhibitory effect can be observed when a distractor is uninformative regarding the subsequent target and disti-actor (e.g.. Chao, 2009b;Chao & Yeh, 2005;Christie & Klein, 2001) and when the predictability of a distractor on the following target is higher than the chance level (e.g.. Chao, 2009b;Chao & Yeh, 2005;Frings & Wentura, 2005;Leboe & Milliken, 2004). Experiment 6 demonstrated that when the precue failed to enable a prediction of the upcoming distractor or target, no effect of a distractor precue benefit or cost was observed.…”
Section: Relation To Other Inhibition-related Phenomenamentioning
confidence: 94%
“…Neill, 2007). In particular, in spatial NP tasks, NP can be found even when targets and distractors are presented with a spatial separation of up to 12°of visual angle (Chao & Yeh, 2005; see also Guy & Buckolz, 2007, for evidence showing that targetdistractor distance seems to play no role in spatial NP), whereas in identity NP tasks, NP usually starts to diminish when the target and distractor are separated by no more than 3°of visual angle (e.g., Fox, 1994;Ruthruff & Miller, 1995). In addition, in identity NP tasks, the selection of a target object in the prime displays often seems to be a precondition for NP to occur (though, see Joordens et al, 2006, for an exception; see also the work by Milliken and colleagues, 1998) whereas, in spatial NP tasks, no selection of a target location is needed for NP to occur (Guy, Buckolz, & Pratt, 2004;Park & Kanwisher, 1994).…”
Section: Np In Different Modalitiesmentioning
confidence: 99%